Congenital lymphatic leukemia / Congenital mastocytosis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2018)
It is not always possible to diagnose clinically congenital infiltrative lesions. At birth, these two children had similar lesions on the nasal-genal groove, but cyto-histological examinations led to a different diagnosis.